Selección de los esquemas y sitios de asociación para mezclas complejas (2016)
This paper shows the selection of schemes and association sites, and also equations of the key property in association terms, made from the hydrogen bonding formation between binary systems of acid + acid, acid + water, alcohol + alcohol and alcohol + water.